Optimization of fuel recovery through the stepwise co-pyrolysis of palm shell and scrap tire - Abnisa, F.; Daud, Wan Mohd Ashri Wan (Elsevier, 2015)
This study optimized the use of biomass waste to generate fuel through co-pyrolysis. In this paper, the effects of stepwise co-pyrolysis temperature and different ratios between palm shells and scrap tires in feedstock were studied to observe any improvements in the quantity and quality of the liquid yield and its byproduct. The ratio of palm shells and scrap tires varied at 100:0, 75:25, 50:50, 25:75, and 0:100. The experiment was conducted in a fixed-bed reactor. The study was divided into two scenarios. The first scenario was performed at the optimum temperature of 500 degrees C with a reaction time of 60 min. In the second scenario, the temperature was set at 500 degrees C for 60 min before the temperature was increased to 800 degrees C with a high heating rate. After the temperature reached 800 degrees C, the condition was maintained for approximately 45 min. Results showed that an increase in the liquid and gas yields was achieved when the temperature increased after optimum conditions. Increased yield was also obtained when the proportion of scrap tire was increased in the feedstock. Several other important findings are discussed in this paper, including the phases of pyrolysis oil, features of the liquid product, and characteristics of the byproducts. All products from both scenarios were analyzed by various methods to understand their fuel characteristics. (C) 2015 Elsevier Ltd. All rights reserved.